A brief look at the Odonata from the Páramo ecosystems in Colombia, with the descriptions of Oxyallagma colombianum sp. nov. and Rhionaeschna caligo sp. nov. (Odonata: Coenagrionidae, Aeshnidae, Libellulidae) - Bota-Sierra, Cornelio Andrés (Zootaxa, 2014)
Here I present the results of field work and collections of Odonata made in several páramos of Colombia between 2007 and 2014. Two undescribed species, in the genera Oxyallagma Kennedy, 1920, and Rhionaeschna Förster, 1909, respectively, were found, as well as two species not previously recorded from Colombia: Rhionaeschna peralta (Ris, 1918) and Oxyallagma dissidens (Selys, 1876). Descriptions and diagnoses of the new species, photographs, maps, illustrations, natural history notes, and comments on morphological plasticity are presented.